Opportunities and barriers for implementation of integrated TB and HIV care in lower level health units: experiences from a rural western Ugandan district - D, Nansera; F, Bajunirwe; J, Kabakyenga; J, Asiimwe PK; H, Mayanja-Kizza (African Health Sciences, 2010)
Background: As countries with a high burden of TB and HIV roll out integrated TB/HIV care, there is need to assess possibility of lower level health units treating TB to provide integrated TB/HIV care. Objective: To determine barriers and opportunities for provision of integrated TB/HIV care in lower level health units offering TB treatment in Mbarara district, Uganda. Methods: Conducted key informant interviews, interviewed health workers and observed services offered. Results: 22 health units were assessed and 88 health workers were interviewed. Of the 18 health units mandated to offer laboratory services, 55.6% and 38.9% were able to offer rapid HIV-testing and ZN staining respectively. Understaffing, lack of capacity to diagnose HIV and TB, lack of guidelines to inform care options of TB/HIV co-infected patients and insufficient knowledge and skills among health workers towards provision of integrated TB/HIV care were mentioned as barriers to provision of integrated TB/HIV services. Conclusion: To offer integrated TB/HIV services at lower level health units currently offering TB stand-alone services, there is need to address gaps in knowledge and skills among health workers, laboratory diagnostics, staffing levels, medical supplies and infrastructure
Keywords: Opportunities; Barriers; Lower health units; Integrated TB/HIV care; Uganda